2018
DOI: 10.1177/1024907918803535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the reliability of scoring systems in the light of histopathological results in the diagnosis of acute appendicitis

Abstract: Background: Acute appendicitis is a very common surgical emergency. Early and correct diagnosis and early intervention are necessary to prevent complications. It is often diagnosed on clinical signs and a certain ratio of negative appendectomy is acceptable. For early and accurate diagnosis, various scoring systems such as Alvarado, Ohmann, Eskelinen and more recently Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) have been developed. Objective: In this study, we aimed to compare the effectiveness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
3
6
2
Order By: Relevance
“…Many studies [14,15,16,17] had documented the sensitivity of RIPASA score taking into consideration a cut-off value of 7.5 and reported a range from 95.5% up to 98.5 % and this is going with the results of the current study which reposted sensitivity of 96.4%. However, this was much higher than Korkut et al [18] and Ozdemir et al [19] , who reported sensitivity of 75% and 68%, respectively. This is assumed to the smaller sample size of their study and the higher cut-off value as they considered 12 and 10, respectively, while 7.5 was the significant cut-off value in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…Many studies [14,15,16,17] had documented the sensitivity of RIPASA score taking into consideration a cut-off value of 7.5 and reported a range from 95.5% up to 98.5 % and this is going with the results of the current study which reposted sensitivity of 96.4%. However, this was much higher than Korkut et al [18] and Ozdemir et al [19] , who reported sensitivity of 75% and 68%, respectively. This is assumed to the smaller sample size of their study and the higher cut-off value as they considered 12 and 10, respectively, while 7.5 was the significant cut-off value in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…The use of a scoring system can assist in diagnosis and ensure prompt and appropriate therapy [10], [17] This study showed that subjects identified as high probability and undergoing emergency surgery generally had complicated appendicitis (64.4%). [19] and Karapolat [11] showing a significant relationship between RIPASA scores and histopathological findings. The RIPASA score is an inexpensive, simple, noninvasive, and rapid scoring system.…”
Section: Discussionmentioning
confidence: 89%
“…Zielke A. etal 1999 carried a study in Germany to validate of the Ohmann score concluded that it has sensitivity (63%), specificity (93%), positive predictive value (77%) and negative predictive value (86%) (19) . Unal Ozdemir Z et al, study 2019 in Turkey found that the sensitivity of Ohmann scoring system was 58% and specificity was 71% (20) . Koppad SN et al, 2016 in Indian study indicated Sensitivity of 96%, specificity 66.7%, positive predictive value 82.8% and negative predictive value of 90.9% (21) .…”
Section: Discussionmentioning
confidence: 98%